2002
DOI: 10.1002/1521-396x(200202)189:2<293::aid-pssa293>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Direct Probe of Induced Magnetic Moments at Interfaces via X-Ray Magnetic Circular Dichroism

Abstract: Recent progress in X-ray magnetic circular dichroism allows us to probe induced magnetism with element specificity and monolayer sensitivity. Here, we demonstrate magnetic polarization of the 5d elements Pt, Ir and W and the 3d V at the interfaces with the 3d ferromagnets Ni and Fe. Pt and Ir are shown to be ferro-while W and V anti-ferromagnetically coupled to Ni or Fe. Spin, orbital and total magnetic moments are obtained and trends in the magnetism of the 5d elements are deduced. Monolayer-resolved magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…In the first method 5 one or more specific Pt layers are replaced by Ir layers, hoping that the induced magnetic moment of the Ir atom ͑which is the neighbor of the Pt atom in the periodic table͒ is essentially the same as the Pt atom would have in a corresponding Pt layer. In the second method 6,7 the average Pt moments of multilayers with different Pt layer thicknesses are subtracted from each other. Assuming that the moments of the various Pt monolayers depend just on the distance from the Co-Pt interface but not on the Pt layer thickness, this yields the Pt magnetization profile.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In the first method 5 one or more specific Pt layers are replaced by Ir layers, hoping that the induced magnetic moment of the Ir atom ͑which is the neighbor of the Pt atom in the periodic table͒ is essentially the same as the Pt atom would have in a corresponding Pt layer. In the second method 6,7 the average Pt moments of multilayers with different Pt layer thicknesses are subtracted from each other. Assuming that the moments of the various Pt monolayers depend just on the distance from the Co-Pt interface but not on the Pt layer thickness, this yields the Pt magnetization profile.…”
Section: Introductionmentioning
confidence: 92%
“…As outlined in the Introduction, this assumption is the basis for a layer-resolved analysis of the induced magnetization profile from the XMCD spectra obtained for various thicknesses of the Pt layer. 6,7 The results of our calculations ͑Fig. 9͒ clearly demonstrate that this assumption is not well justified for small layer thicknesses which are essential for the determination of the magnetization profile.…”
Section: Magnetization Profile In the Pt Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Also included in this figure is the mean value of the Pt moment, M Pt ¼ 0:6ð3Þ m B =atom, inserted as a horizontal line. Thus, as expected, the induced Pt moment is aligned parallel with the FeCo moments [20]. Previous studies on Co/Pt multilayers revealed an interface Pt magnetic moment in the range of 0:220:7 m B =atom [6,21,22].…”
Section: Article In Pressmentioning
confidence: 99%
“…2 However, during the last decade, the development of techniques with element specificity and monolayer sensitivity, such as x-ray magnetic circular dichroism ͑XMCD͒, 3 permits a more systematic study of induced ferromagnetism in thin multilayer structures. To date, most efforts have been focused on the induced magnetic moments of the 3d, 4d, and 5d transition-metal series, 4 whereas the induced magnetism of 5f elements in magnetic multilayers is still largely unexplored. Indeed, the combination of a soft magnetic element like iron and an element that possesses a large spin-orbit coupling, such as uranium, may give rise to interesting and unusual magnetic properties.…”
Section: Introductionmentioning
confidence: 99%